Properties of set-valued stochastic differential equations. (1st December 2016) - Kisielewicz, Michał; Michta, Mariusz
Abstract : The paper is devoted to properties of set-valued stochastic differential equations. The main result of the paper deals with existence and uniqueness of solutions. Furthermore, a connection between solutions of stochastic differential inclusions and solutions of set-valued stochastic differential equations are given. The result of the paper extends a lot of particular results dealing with such type equations.